Secondary forest and shrubland dynamics in a highly transformed landscape in the Northern Andes of Colombia (1985-2015) (2017)
Understanding the dynamics of natural ecosystems in highly transformed landscapes is key to the design of regional development plans that are more sustainable and otherwise enhance conservation initiatives. We analyzed secondary forest and shrubland dynamics over 30 years (1985-2015) in a densely populated area of the Colombian Andes using satellite and biophysical data. We performed a land-cover change analysis, assessed landscape fragmentation, and applied regression models to evaluate the effects of environmental and geographical correlates with the observed forest transitions. Forest cover area increased during the 30 year-span, due mostly to forest regrowth in areas marginal for agriculture, especially during the first half of the study period. However, a high dynamic of both forest regrowth and clearing near urban centers and roads was observed. Soil fertility turned out to be a key correlate of both forest recovery and deforestation. Secondary forests, <30 years old represent the most fragmented component. Our findings reflect the complexity of the processes occurring in highly transformed and densely populated regions. Overall, this study provides elements for a better understanding of the factors driving land cover change near large urban areas, and raises new iideas for further research. © 2017 by the author.